Emotional Intelligence Associated with Reduced Academic Stress in Adolescents: Kecerdasan Emosional Berkaitan dengan Pengurangan Stres Akademik pada Remaja - Nur Wardatur Rohmah; Nurfi Laili Laili (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic stress is a psychological condition experienced by adolescents due to academic demands, achievement pressure, and fear of academic failure. Specific Background: Emotional intelligence involves the ability to recognize, regulate, and manage emotions, which supports student adaptation to academic challenges. Knowledge Gap: Empirical evidence examining the correlation between emotional intelligence and academic stress among junior high school students remains limited. Aims: This study examined the relationship between emotional intelligence and academic stress among grade 9 students at SMP Negeri 1 Wonoayu. Results: This quantitative correlational study involved 182 students selected through quota sampling. Data were collected using the Emotional Intelligence Scale (30 items; α = 0.881) and Academic Stress Scale (21 items; α = 0.91), analyzed using Pearson product moment correlation. Findings showed a significant negative correlation between emotional intelligence and academic stress (r = -0.016; p = 0.035). Most students demonstrated moderate levels of academic stress (64%) and emotional intelligence (65%), with emotional intelligence contributing 2.6% to academic stress variability. Novelty: This study provides empirical evidence focusing on junior high school students, expanding research beyond university populations. Implications: Emotional intelligence development may be considered in student psychological support to manage academic pressure. Highlights: Statistical Testing Revealed a Significant Inverse Association Between Psychological Self-Regulation Ability and Learning Pressure. Majority of Participants Demonstrated Moderate Levels of Learning-Related Tension and Socio-Emotional Competence. Emotional Self-Management Accounted for a Small Proportion of Variability in Learning-Related Strain. Keywords: Emotional Intelligence, Academic Stress, Adolescent Students, Psychological Adaptation, School Pressure